Generalised differential operator defined by analytic functions associated with negative coefficients - S. Faraj Ramadan,; Maslina Darus, (Penerbit Universiti Kebangsaan Malaysia, 2010)

(untitled)
We define a new generalised derivative operator Dm,s,µ,b for the class A of analytic functions in the unit disc U = {z∈C:|z|<1} . This operator has generalised many well known operators studied by many different authors. Also in this paper we introduce a new subclass of A using generalised derivative operator. Coefficient inequalities, distortion theorems, and extreme points of analytic functions belonging to the subclass are given